Passively Q-switched thulium-doped fiber laser with silver-nanoparticle film as the saturable absorber for operation at 2.0 µm. (2nd November 2016) - Ahmad, H; Samion, M Z; Muhamad, A; Sharbirin, A S; Ismail, M F
Abstract: In this work, a compact thulium-doped fiber laser with a Q-switched output is proposed and demonstrated. A thulium-doped fiber is used for the laser, with a peak absorption of 200 dB m −1 at 790 nm and a cutoff wavelength of 1350 nm as the primary gain medium, and a silver-based saturable absorber as the pulse generation mechanism. The pulses obtained from the proposed laser have repetition rates from 38.3 kHz up to 56.2 kHz, with a pulse width as low as 4.2 µ s and pulse energy as high as 67.3 nJ at a maximum pump power of 228.8 mW. The generated pulses are highly stable, showing no changes or fluctuations over operation for a period of 60 min, and further validated with signal-to-noise ratios of 57.0 dB and 59.5 dB in the optical and frequency domains respectively. The proposed laser has high potential for eye-safe applications in manufacturing and medicine.